PP297 Rethinking The Gap Between Technology And Implementation: A Framework For Socially Embedded Technoscience. (December 2020) - Andrews, Chad
Abstract : Introduction: In 1964, Jacques Ellul framed the history of technology as one defined not just by the introduction of new machines, but by the social and institutional practices that guide their use and implementation. He called this integrated system "la technique, " believing that the word "technology" had come to emphasize physical tools at the cost of social ones. There is a strong critical component in Ellul, who opposed the dehumanization apparent in technological systems and their associated forms of utilitarian thinking. Remaining aware of this critical history, this study relies on Ellul and similar technological theories to conceptualize a framework for rethinking the distinction between health technologies and their implementation in the context of health technology assessments (HTAs). It does so by considering how HTAs could be modified within the proposed framework to better consider the social and human factors that determine how a drug or technology exists within a "live" social environment. Methods: The study is conceptual and driven by an analysis of existing HTAs. It details potential ways that reviews could be adjusted in line with the presentation's proposed framework. Results: By collapsing the distinction between technology and implementation, we can guide HTAs that are more cognizant of the essential human and social components of implementation, helping to avoid the crises that arise when technologies are introduced without considering their fundamental social factors. Conclusions: Many modern HTAs already take implementation into account, but their findings treat technologies as conceptually distinct from practices and procedures, leaving the latter to local institutions to determine. By challenging the traditional gap between technological and sociological factors in traditional HTA practices, it is possible to develop new approaches to reviewing health technologies—not as distinct objects, but as complex sociotechnical phenomena in line with Ellul's "la technique."